Leaf anatomy and histochemistry of three species of Ficus sect. Americanae supported by light and electron microscopy - Araújo, Nathalia Diniz; Coelho, Victor Peçanha M.; Ventrella, Marília Contin; Agra, Maria de Fátima (Microscopy and Microanalysis, 2013)
In this work the leaf anatomy of three species of Ficus section Americanae (Miq.) Miq. from Brazil, whose leaves and latex are used in folk medicine is reported. The work was carried out using light and scanning electron microscopy in order to characterize these species and to evaluate their taxonomic significance, and also contribute to the quality control of their ethnodrugs. The three species (Ficus cyclophylla, Ficus elliotiana, and Ficus caatingae) showed hypostomatic leaves, anomocytic stomata, straight epidermal cell outlines, and a dorsiventral mesophyll. Some micro-morphological characters such as density and distribution of epicuticular waxes, glandular trichomes, the length and width of stomata, as well as the palisade of mesophyll and petiole outlines proved to be the most useful and distinctive characters for the separation of species. These may contribute as additional support for the taxonomy of the section and for the quality control of their ethnodrugs.
Keywords: Ficus subg. Urostigma; Moraceae; SEM; Medicinal plants; Ficus cyclophylla; Ficus elliotiana; Ficus caatingae